1997
DOI: 10.1128/jb.179.22.7169-7173.1997
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for transcription attenuation rendering cryptic a sigmaS-dependent promoter of the osmotically regulated proU operon of Salmonella typhimurium

Abstract: The osmotically regulated proU locus in Escherichia coli has two promoters, P1 and P2, that are recognized, respectively, by the S -and 70 -bearing RNA polymerase holoenzymes. However, the equivalent of the P1 promoter does not appear to exist in Salmonella typhimurium. We demonstrate in this study that wild-type S. typhimurium has a cryptic P1 promoter that is recognized by S RNA polymerase in vitro and that a 22-bp deletion from ؉63 to ؉84 (relative to the start site of transcription) confers S -dependent in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

1998
1998
2003
2003

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…As explained above, all lac expression values were obtained in, and are reported for, pairs of isogenic rpoS ϩ and rpoS derivatives, whose difference has been taken to represent the in vivo activity of the RpoS-dependent proU P1 promoter under the particular test conditions; by these criteria, the plasmid vectors pMU575 and pMU2385 carrying the promoterless lacZ reporter gene displayed insignificant RpoS-dependent lac expression under any of the conditions tested in this study (data not shown). It may also be noted that the in vivo proU P1 activation studies were not amenable to analysis by mRNA primer-extension experiments, in light of our earlier findings (16,42) that even the cryptic promoter in both S. enterica and E. coli exhibits normal transcription initiation.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…As explained above, all lac expression values were obtained in, and are reported for, pairs of isogenic rpoS ϩ and rpoS derivatives, whose difference has been taken to represent the in vivo activity of the RpoS-dependent proU P1 promoter under the particular test conditions; by these criteria, the plasmid vectors pMU575 and pMU2385 carrying the promoterless lacZ reporter gene displayed insignificant RpoS-dependent lac expression under any of the conditions tested in this study (data not shown). It may also be noted that the in vivo proU P1 activation studies were not amenable to analysis by mRNA primer-extension experiments, in light of our earlier findings (16,42) that even the cryptic promoter in both S. enterica and E. coli exhibits normal transcription initiation.…”
Section: Resultsmentioning
confidence: 99%
“…In an earlier study (42), we had shown that the in vivo expression from an S. enterica proU P1 promoter fragment extending from Ϫ66 to ϩ117 (S. enterica P1) of the lacZ reporter gene borne on a very low-copy-number plasmid (pHYD373) is prevented because of transcription attenuation occurring some distance downstream of the site of transcription initiation. Attenuation was relieved, and lacZ expression was consequently observed, in strains carrying a mutant plasmid derivative (pHYD374) that had suffered a 22-bp deletion between nucleotides ϩ63 and ϩ84 relative to the transcription start site (S. enterica P1⌬att).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations